Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 24. Beitrag: Neuroptera. - Zeleny, Jiří (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The author presents the results of his investigations on the order Neuroptera of Albania. The material collected by the expedition of the Deutsches Entomologisches Institut contained 67 specimens of this order representing 17 species, 9 of which were new to the fauna of Albania.